A function-driven characterization of printed conductors on PV cells. (16th May 2018) - Bellotti, Roberto; Furin, Valentina; Maras, Claire; Picotto, Gian Bartolo; Ribotta, Luigi
Abstract: Nowadays the development in photovoltaic (PV) cells manufacturing requires increasingly sophisticated technologies, and in order to avoid efficiency losses in PV cell, printing techniques of the front contacts have to be well controlled. To this purpose, printed linear conductors (PLCs) on a PV standard cell are characterized by morphology- and resistance-based measurements, creating a well-calibrated test structure towards the development of an application-oriented material measure. It can be noticed that morphology and texture parameters determined by stylus and optical profilers are well in agreement, and the resistance calculated from the reconstructed cross-section area matches quite well the measured resistance of fingers. Uncertainties of about 14% to 17% are estimated for local measurements of morphology-based and measured resistance of finger segments up to 5 mm length. Fingers characterized by somewhat larger roughness/waviness values (, , ) show some local irregularities, which may degrade the electrical contact of the PV front surface.